THE EFFECT OF USING ENGLISH SONG TOWARDS STUDENTS’ VOCABULARY MASTERY - Astuti, Anggi Yuli (Universitas Mahaputra Muhammad Yamin, 2023)
The aim of this study was to investigate the impact of incorporating English songs in teaching on the vocabulary proficiency of fourth-grade students at SD IT Cahaya Madani. The motivation for the study was due to the challenges that students faced in mastering English vocabulary, including disinterest and lack of motivation, limited vocabulary, and perceived difficulty in understanding the language. To address these challenges, the researcher used a quantitative approach with a quasi-experimental research design that involved two classes, the fourth Abu Ubaidah class (control) and the fourth Umar class (experimental), both comprising 27 students. Each class did the pre-test and post-test. The vocabulary test was the main research instrument, and the data was analyzed using the independent sample T-test in SPSS 26. The findings revealed a significant difference in the vocabulary proficiency of students who were taught with English songs compared to those who were not. The t-table was 2.059, which was smaller than the t-obtained (16.694). It means using English song enables students improve their vocabulary mastery, make fun learning and avoid stressful. Suggesting that the use of English songs had a significant impact on the students' vocabulary mastery.